2019
DOI: 10.3390/f10090772
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Phosphate-Solubilizing Bacteria and N2-fixing Bacteria on Nutrient Uptake, Plant Growth, and Bioactive Compound Accumulation in Cyclocarya paliurus (Batal.) Iljinskaja

Abstract: Research Highlights: We firstly interpreted nutritional mechanisms involved in growth regulation and phytochemical accumulation in Cyclocarya paliurus (Batal.) Iljinskaja under three inoculant types, and selected bacterial inoculations for multiple purposes of C. paliurus plantation. Co-inoculation with phosphate-solubilizing bacteria (PSB) and N2-fixing bacteria (NFB) performed better in growth promotion and nutrient uptake than single bacterial inoculation. Background and Objectives: C. paliurus is a well-kn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(31 citation statements)
references
References 53 publications
7
19
0
Order By: Relevance
“…This study found that the effect of PSBs on soil nutrient content was significantly different. Compared to the control, the content of TN, TP, TK, AP and AK increased significantly, demonstrating that PSB elevated the amounts of available N, P, and K in the soil and subsequently provided better nutrition for plant growth 60 , 61 , which is consistent with the results of Matsumura et al 62 and Wang et al 63 found that inoculation with PSBs significantly increased the accumulation of available phosphorus and nitrogen in the soil, and effectively promoted the growth of Willow seedlings.…”
Section: Discussionsupporting
confidence: 89%
“…This study found that the effect of PSBs on soil nutrient content was significantly different. Compared to the control, the content of TN, TP, TK, AP and AK increased significantly, demonstrating that PSB elevated the amounts of available N, P, and K in the soil and subsequently provided better nutrition for plant growth 60 , 61 , which is consistent with the results of Matsumura et al 62 and Wang et al 63 found that inoculation with PSBs significantly increased the accumulation of available phosphorus and nitrogen in the soil, and effectively promoted the growth of Willow seedlings.…”
Section: Discussionsupporting
confidence: 89%
“…In addition, the decrease in soil nutrient content at last time points may also be due to seasonal variation and nutrient uptake by plants. Our previous study confirmed that these microbial inoculants enhanced nutrient uptake and stimulated plant growth and biomass accumulation after whole inoculation procedures (32). (29).…”
Section: Discussionsupporting
confidence: 81%
“…Although this work provided the detailed information about how inoculation period and type affect the resident microbes, the future study should consider to set a unique control which receives only one dose at first and sampled at the end of experiment, to further compare the influences of repeated inoculation compared to one-off inoculation. Furthermore, insignificant (46) (32). However, it cannot be ruled out that other factors, not assessed in this study, might be driving this seasonal variation.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…In contrast to the well-documented action of phosphate-solubilizing and nitrogen-fixing microorganisms in plant P and N nutrition [ 13 , 14 ], the importance of microbial activity on plant K nutrition is less well understood. It has been shown that bacteria and mycorrhizal fungi do solubilize mineral K by various mechanisms such as production of alkaline substances including ammonia and other metabolites upon death of microbial cells and subsequent proteolysis [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%